Constructal view of the scaling laws of street networks — the dynamics behind geometry - Reis, A. Heitor (2012)
The distributions of street lengths and nodes follow inverse-power distribution laws. That means that the smaller the network components, the more numerous they have to be. In addition, street networks show geometrical self-similarities over a range of scales. Based on these features many authors claim that street networks are fractal in nature. What we show here is that both the scaling laws and self-similarity emerge from the underlying dynamics, together with the purpose of optimizing flows of people and goods in time, as predicted by the Constructal Law. The results seem to corroborate the prediction that cities’ fractal dimension approaches 2 as they develop and become more complex.